FORMULASI KEBIJAKAN PENDIDIKAN GRATIS KABUPATEN PELALAWAN TAHUN 2013 - ", Darwis; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study analyzes the formulation of Free Education Policy in Pelalawan at 2013. This research is used as a consideration object by the relevant agencies in formulating a policy, and located in Education Office, Regional Representatives Council (DPRD), and the Regional Secretariat of Pelalawan district. This research used qualitative method such as descriptive analysis with relevant data sources consisting of primary data and secondary data. In collecting the data the author used interview, observation, and documentation technique that called purposive sampling, with people who are experts and understand with phenomena that occur. This study shows that, the Free Education Policy Formulation in Pelalawan at 2013 consists of four steps, such as: the actors who involved, preferences of the actors of development policy, social base of the actors, and the resources of policy actors. The free education policy in the form of regent regulations No. 13 of 2013 concerning the delivery of free education. Keywords: Formulation, Free Education Policy, regent regulations